MEDIA SOSIAL DAN KETOPRAK - Mudjijono Mudjijono (Jantra., 2017)
Social media has been rapidly developing. It can be used in various fields, such as government, education, and traditional performing art. This study looks at how social media is utilized to support ketoprak a traditional play that is still living in the society. The data were collected from library research and from interviews with resource persons who know about the past history of ketoprak. The analysis was based on the concept of tradition by Shil and collective conscience by Durkheim.